Modi energising a green future - Edited by Pachnanda, R. K....et.al. (New Delhi Pentagon Press, 2023)
Climate change and energy security are interconnected and are two sides of the same coin. The increasing share of non-hydrocarbon or non-fossil energy, as evidence suggests, will help in significant reduction in carbon emissions. There is now broadly a global drive to expand energy sources and increase energy efficiency, both in distribution and consumption in order to mitigate climate change, reduce energy dependency, and minimize energy price volatility. India has shown the world what it takes to be a climate leader. The UN Environment Programme in 2018 recognized Prime Minister Modi for his bold environmental leadership on the global stage. Energy transition will be the most important pillar for climate action for the country and for this India is rapidly crafting a sturdy ecosystem to enable the transformation through technology readiness, capacity upgrade, climate finance, regulatory reforms and new and innovative business models, which will together help in achieving India`s climate and sustainable development goals. This volume presents a well-integrated collection of chapters from distinguished decision-makers, influential opinion makers, and eminent experts creating in the process a synergy of views supporting India`s transition to affordable and sustainable energy that not only reduces emissions, but spurs economic growth and promotes sustainable climate investments.
Keywords: Prime minster; Climate Change